2012
DOI: 10.1371/journal.pone.0037319
|View full text |Cite
|
Sign up to set email alerts
|

What Role Do Annelid Neoblasts Play? A Comparison of the Regeneration Patterns in a Neoblast-Bearing and a Neoblast-Lacking Enchytraeid Oligochaete

Abstract: The term ‘neoblast’ was originally coined for a particular type of cell that had been observed during annelid regeneration, but is now used to describe the pluripotent/totipotent stem cells that are indispensable for planarian regeneration. Despite having the same name, however, planarian and annelid neoblasts are morphologically and functionally distinct, and many annelid species that lack neoblasts can nonetheless substantially regenerate. To further elucidate the functions of the annelid neoblasts, a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Typically, in addition to the prostomium, a fixed number of segments are regenerated ("head segments" in clitellates) but these segments all differentiate more or less at the same time. For example, in Enchytraeus japonicus, where asexual reproduction by fission occurs in addition to anterior and posterior regeneration, a prostomium plus seven head segments are regenerated when the worm is amputated of more than seven anterior segments (Myohara, 2012). By contrast, if the worm is amputated within the "head region", i.e.…”
Section: Regeneration Of Segments: Two Distinct Pathwaysmentioning
confidence: 99%
“…Typically, in addition to the prostomium, a fixed number of segments are regenerated ("head segments" in clitellates) but these segments all differentiate more or less at the same time. For example, in Enchytraeus japonicus, where asexual reproduction by fission occurs in addition to anterior and posterior regeneration, a prostomium plus seven head segments are regenerated when the worm is amputated of more than seven anterior segments (Myohara, 2012). By contrast, if the worm is amputated within the "head region", i.e.…”
Section: Regeneration Of Segments: Two Distinct Pathwaysmentioning
confidence: 99%
“…the description of neoblasts have been described mostly in clitellates, but also in some polychaetes (Bilello & Potswald, 1974;Cornec, Cresp, Delye, Hoarau, & Reynaud, 1987;Faulkner, 1929Faulkner, , 1932Krecker, 1923;Probst, 1931;Randolph, 1891Randolph, , 1892Stephan-Dubois, 1954;Stolte, 1929;Sugio et al, 2008;Tadokoro, Sugio, Kutsuna, Tochinai, & Takahashi, 2006;Zattara, Turlington, & Bely, 2016). Regeneration abilities are not limited to species with neoblasts; annelids that lack cells with obvious neoblast characteristics can regenerate (Herlant-Meewis, 1964;Krecker, 1923;Myohara, 2012;Stone, 1933). The role of neoblasts in annelid regeneration has not been experimentally tested.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a population of ‘set‐aside’ stem cells, or neoblasts , contributes to the blastemal tissue in annelid regeneration (Krecker, ; Randolph, ). It was recently shown that regeneration is incomplete but not totally abolished in the Enchytraeus species lacking neoblast (Myohara, ). Furthermore, knockdown of grimp , a gene expressed in the neoblasts, leads to impaired regeneration in mesoderm, but not in ectoderm and endoderm (Takeo, Yoshida‐Noro, & Tochinai, ).…”
Section: Loss Of Regenerative Capability In the Leechmentioning
confidence: 99%
“…The developmental fates of the early and standard m blast cells are the same as the leech, but the supernumerary blast cells may give rise to the stem cells in the PGZ nelid regeneration (Krecker, 1923;Randolph, 1892). It was recently shown that regeneration is incomplete but not totally abolished in the Enchytraeus species lacking neoblast (Myohara, 2012).…”
Section: Loss Of Reg Ener Ative C Apab Ilit Y In the Leechmentioning
confidence: 99%